Developing an institutional language policy in the complex scenario of internationalization - Clark, Caroline (Verbum, 2022)
Over the last 20 years since the Bologna Agreement the role of language in Higher Education has gained recognition as an integral part of the teaching/learning process, and an essential element of the process of internationalization. The rapid shift towards internationalization has had a pronounced effect on academic life, procedure, and personnel. In this process, it has often become the role of Language Centres to organize the language aspect, and to a more limited extent, to advise on language.This short paper looks at the involvement of the University of Padova Language Centre (CLA) in the process of internationalization, and in particular the promotion of a language policy. A project developed to promote language and teaching methodology courses for academic staff required to teach in English, and the findings of research based on this project, led to recognition of the need to draft a language policy which encompasses the wide-ranging issues relevant to successful internationalization.